Qualitative Content Analysis of Soft-Selling Marketing Messages in The Short Film “Pulang” - Arief Oscar Navero; Nicholas Pranata (Fakultas Film dan Televisi - Institut Kesenian Jakarta, 2026)
In the post-pandemic era, public utilities and transportation services have faced challenges in rebuilding customer trust. PT Kereta Api Indonesia (Persero) addressed this by creating a branded short film,